Assessment of performance and safety of Corneal Chamber hypothermic storage medium and PSS-L corneal rinsing solution in human and porcine corneas - Laura Giurgola; Claudio Gatto; Stefano Ferrari; Eugenio Ragazzi; Claudia Honisch; Orietta Rossi; Jana D'Amato Tothova; Umberto Rodella; Paolo Ruzza (BMJ Open Ophthalmology)
Purpose To prove the safety and performance of the hypothermic corneal storage medium 'Corneal Chamber' and the rinsing solution 'PSS-L' in support of the new Conformité Européenne (CE) certification process in accordance with the Medical Device Regulation.Methods Fifteen (n=15) human donor corneas and 11 (n=11) porcine corneas were evaluated for the following parameters: endothelial cell density (ECD) and mortality, percentage of hexagonal cells (HEX%), coefficient of cellular area variation (CV%) and corneal transparency at Day 0 and after 14±1 days of storage in Corneal Chamber medium at 2–8°C. Then, the same parameters were assessed after rinsing of corneas in PSS-L for 1 min at room temperature. Evaluation of gentamicin sulfate carryover after corneal storage and PSS-L rinsing was performed by ultra-high performance liquid chromatography analysis on human corneas homogenates.Results Human and porcine corneas stored in Corneal Chamber medium showed a good overall quality of the tissue according to the quality parameters evaluated. In particular, mean ECD, HEX% and CV% did not show statistically significant changes at the end of storage and endothelial mortality increased to 3.1±3.3 and 7.8±3.5% in human and porcine corneas, respectively. Tissue rinsing with PSS-L did not affect the quality parameters evaluated before and gentamicin sulfate residues were absent in human corneas.Conclusions Corneal preservation in Corneal Chamber medium at 2–8°C for 14 days and the corneal rinse with PSS-L are safe and effective procedures allowing the preservation of the corneal quality parameters as well as the complete elimination of gentamicin sulfate from the tissues before transplantation.Cite Now